Business Plan : Bastique Art Enterprise / Muhammad Muzhaffar Aris , Hanisah Jais & Nurfarhanna Rosli - Aris, Muhammad Muzhaffar; Jais, Hanisah; Rosli, Nurfarhanna (2009)
Our company’s name is Bastique Art Enterprise. This business will be operated in Sunway Lagoon Theme Park,Bandar Sunway. In specifically, the business is located at Lot 007 Jalan PJS 11 /11. Bandar Sunway 46150 Petaling Jaya.The target of our business commencements is on 1st January 2009. Bastique Art basically provides souvenir and gift customer who comes to Sunway Lagoon Theme Park. Our shop main products are the photo memory where it is not just be printed on paper, but also, can be printed on our other merchandise such as key chains, t-shirL mugs and teddy bear. Customer can also try our ‘Fantasy Photo’.whereby they can choose any location, situation, famous people or even biggest event to be with them just in our very own photo studio. There are few factors why we select this business. Firstly h to- fulfill the people needs and wants especially the tourist. Besides that we also aimed in becoming the greater photo shops in future.